2009
DOI: 10.1088/1475-7516/2009/01/024
|View full text |Cite
|
Sign up to set email alerts
|

A minimal set of invariants as a systematic approach to higher order gravity models

Abstract: Higher-order gravity models have been recently the subject of much attention in the context of cosmic acceleration. These models are derived by adding various curvature invariants to the EinsteinHilbert action. Several studies showed that these models can have late-time self-acceleration and could, in some cases, fit various observational constraints. In view of the infinite spectrum of invariants that could be built from curvature tensors, we propose here a method based on minimal sets of independent invarian… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 67 publications
1
28
0
Order By: Relevance
“…which is consistent with the field equation in [22]. Thus, for a Lagrangian density dependent on the traceless…”
Section: Iii51 Traceless Ricci Squaresupporting
confidence: 86%
“…which is consistent with the field equation in [22]. Thus, for a Lagrangian density dependent on the traceless…”
Section: Iii51 Traceless Ricci Squaresupporting
confidence: 86%
“…The method is based on a connection made between theorems in invariants theory in relativity and higher-order cosmological models. We outline here the major ideas of this method and refer the reader to [4] for the detail. The method involves the identification of the Petrov type corresponding to the symmetry of the spacetime, e.g.…”
Section: Higher-order Gravity Models Based On Minimal Setsmentioning
confidence: 99%
“…The corresponding dynamics allows for some models to have late-time self-acceleration without the need for a cosmological constant or other forms of dark energy. In previous work [4], the authors were able to show a range of these models in the basis {R, R1} that showed self-acceleration at late times using numerical and analytical methods. The discussion there focused on power-law type solutions with late-time acceleration free from separatrix singularities, so that the models can transition from a matter dominated phase to the desired cosmic acceleration phase seen by current observations.…”
Section: Higher-order Gravity Models Based On Minimal Setsmentioning
confidence: 99%
See 2 more Smart Citations